Modeling liquid, three-dimensional modeling kit, and method for manufacturing three-dimensional object
By using single-function and multifunctional copolymer mold liquid in three-dimensional modeling, the problem of insufficient strong ion tendency and thermal decomposition performance of water-soluble mold liquid in the prior art when treating easily oxidized metal powders is solved, and the excellent strength and thermal decomposition performance of green bodies are achieved, and the sintering density and production efficiency are improved.
Patent Information
- Application Number
- JP2021036820
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-03-09
AI Technical Summary
The water-soluble mold liquid used in the existing three-dimensional modeling has a strong ion tendency when treating metal powders that are prone to oxidation, making it difficult to form green bodies with excellent strength and thermal decomposition properties.
A mold liquid containing single-function and multifunctional copolymers is used, wherein the monofunctional copolymer is a pyrolytic copolymer, and the mass ratio of the monofunctional copolymer and the multifunctional copolymer is between 65/35 and 95/5, and the thermal decomposition residue of the mold liquid is 5% or less.
A green body with excellent strength and thermal decomposition performance is achieved, which avoids sintering obstacles caused by insufficient thermal decomposition, improves density and performance, simplifies the oil removal process, and improves production efficiency.
Smart Images

Figure 0007647182000006 
Figure 0007647182000007 
Figure 0007647182000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a modeling liquid, a kit for three-dimensional modeling, and a method for manufacturing a three-dimensional object. [Background technology]
[0002] Conventionally, in 3D modeling using metal powder, a water-soluble modeling liquid in which a water-soluble resin such as polyvinyl alcohol (PVA) or polyvinylpyrrolidone (PVP) is dissolved in a water-based solvent has been widely used. However, such water-soluble modeling liquids have a high ionization tendency of aluminum, magnesium, etc., and it is difficult to apply them to 3D modeling using metal powder that is easily oxidized.
[0003] In order to solve the above problems, attempts have been made to apply a cross-linking modeling liquid containing a cross-linking agent and an organic solvent as a modeling liquid for resin-coated metal powder. By resin-coating the metal powder, the resin content in the green body is increased, and the strength of the green body can be increased.
[0004] Also, a material for use in a three-dimensional printing method, which contains a dry particulate material, a liquid monomer, and an initiator, has been proposed (see, for example, Patent Document 1). Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a molding liquid capable of molding a green body having excellent strength and thermal decomposition property. [Means for solving the problem]
[0006] The present invention provides a method for solving the above problems. Create a green body to be used for 3D modeling The modeling liquid contains a monofunctional monomer and a polyfunctional monomer, and the monofunctional monomer contains a thermally decomposable monomer. The mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is 65 / 35 to 95 / 5, and the content of the thermally decomposable monomer is 5% by mass or more 20% by mass or less, and the rate of pyrolysis residue in the resin film of the modeling liquid is 5% by mass or less. Effect of the Invention
[0007] According to the present invention, it is possible to provide a molding liquid capable of molding a green body having excellent strength and thermal decomposition property. [Brief description of the drawings]
[0008] [Figure 1A] FIG. 1A is a schematic diagram showing an example of the operation of a three-dimensional object manufacturing apparatus used in the three-dimensional object manufacturing method of the present invention. [Figure 1B] FIG. 1B is a schematic diagram showing another example of the operation of the apparatus for manufacturing a three-dimensional object used in the method for manufacturing a three-dimensional object of the present invention. [Figure 1C] FIG. 1C is a schematic diagram showing another example of the operation of the apparatus for manufacturing a three-dimensional object used in the method for manufacturing a three-dimensional object of the present invention. [Figure 1D] FIG. 1D is a schematic diagram showing another example of the operation of the apparatus for manufacturing a three-dimensional object used in the method for manufacturing a three-dimensional object of the present invention. [Figure 1E] FIG. 1E is a schematic diagram showing another example of the operation of the apparatus for manufacturing a three-dimensional object used in the method for manufacturing a three-dimensional object of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, "powder" may also be referred to as "powder" or "powder material". "Modeling liquid" may also be referred to as "hardening liquid" or "reaction liquid". A three-dimensional object formed by laminating hardened materials may also be referred to as a "green body", "sintered body", "molded body", or "modeled object". A "green body" that has been heat-treated and degreased may also be referred to as a "degreased body". The "green body" and "degreased body" may collectively be referred to as a "sintering precursor".
[0010] (modeling liquid) The molding liquid of the present invention is a molding liquid containing a monofunctional monomer and a polyfunctional monomer, wherein the monofunctional monomer includes a thermally decomposable monomer, the mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is 65 / 35 to 95 / 5, the thermal decomposition residue rate in the resin film of the molding liquid is 5 mass% or less, and further contains other components as necessary.
[0011] In conventional cross-linkable modeling liquids, the resin that coats the metal powder must be plasticized with an organic solvent to increase reactivity, so the coating resin and the organic solvent must be compatible. In addition, when the compatibility between the coating resin and the organic solvent is high, the conventional cross-linkable modeling liquid has a problem that the non-modeling parts to which the modeling liquid has not been applied come into contact with the vapor of the organic solvent during the drying process, causing the non-modeling parts to harden.
[0012] The material described in the conventional Patent Document 1 (JP Patent No. 4624626) uses the hardened material obtained by the 3D printing method as it is without sintering, and does not disclose the composition of the hardened material suitable for degreasing and sintering. There are no specific examples of reactive monomers to be used, and the thermal decomposition of the green body is not disclosed. If the thermal decomposition of the green body is poor, the sintering itself may not proceed, and even if sintering is possible, there is a problem that the density of the sintered body is low.
[0013] The molding liquid of the present invention contains a monofunctional monomer and a polyfunctional monomer, and contains a thermally decomposable monomer as the monofunctional monomer, and the mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is 65 / 35 to 95 / 5, and the thermal decomposition residue rate in the resin film of the molding liquid is 5 mass% or less. Therefore, the obtained green body has excellent thermal decomposition properties, and therefore no sintering inhibition occurs in the sintering step, and a molded object (sintered body) with good density, strength, thermal conductivity, electrical conductivity, etc. can be obtained. In addition, because the green body has excellent thermal decomposition properties, the time required for the degreasing step can be shortened, and productivity is increased. Furthermore, in the present invention, there is no need to use a cleaning liquid (wet removal) to remove the adhesion of the non-shaped parts from the green body, and dry removal can be performed, so productivity is high and no by-products (waste liquid) are generated. However, in the case of wet removal, a drying process is required, which is time-consuming and reduces productivity.
[0014] In the present invention, the rate of pyrolysis residue in the resin film of the modeling liquid is 5.0% by mass or less, preferably 4% by mass or less, and more preferably 3% by mass or less. The resin film of the modeling liquid is a hardened body formed by applying heat to the modeling liquid alone. It is sufficient that a certain shape is maintained, and the shape is not limited to a film shape. When the rate of pyrolysis residue in the resin film of the modeling liquid is 5.0 mass % or less, a green body with excellent pyrolysis properties can be obtained. Here, the rate of pyrolysis residue in the resin film of the modeling liquid can be measured as follows. 2 g of the modeling liquid is placed in a Teflon (registered trademark) petri dish with a diameter of 5 cm, and treated for 6 hours in a thermostatic chamber at 80 ° C. with nitrogen gas filled and oxygen concentration of 5 volume % or less to obtain a resin film. 8 mg of the obtained resin film is weighed out, and the temperature is raised from 50 ° C. to 450 ° C. at a heating rate of 20 ° C. / min with a nitrogen gas flow of 200 ml / min using a thermal analysis device Thermoplus EVOII and a differential type differential thermobalance TG-DTA (manufactured by Rigaku Corporation). After holding at 450 ° C. for 30 minutes, the residue weight is obtained, and the thermal decomposition residue rate can be calculated using the following formula. Pyrolysis residue rate (%) = (residue weight / weight before TG measurement) × 100
[0015] The molding liquid of the present invention contains a monofunctional monomer and a polyfunctional monomer, and further contains other components as required. By using the above-mentioned molding liquid, a green body having strength and thermal decomposition properties suitable for the debinding and sintering steps can be obtained.
[0016] <Monofunctional monomer> Examples of the monofunctional monomer include a thermally decomposable monomer and a monomer having an alicyclic structure in the side chain.
[0017] -Thermolybdic Monomer- The thermally decomposable monomer means a monomer that leaves a thermal decomposition residue in the resin film of the monomer at a rate of 1 mass % or less. Here, the rate of pyrolysis residue of the resin film of the monomer can be measured as follows. 2 g of the monomer solution containing the monomer and polymerization initiator is placed in a Teflon (registered trademark) petri dish with a diameter of 5 cm, and treated for 6 hours in a thermostatic chamber at 80 ° C. with nitrogen gas filled and oxygen concentration of 5 volume % or less to obtain a resin film. 8 mg of the obtained resin film is weighed out, and the temperature is raised from 50 ° C. to 450 ° C. at a heating rate of 20 ° C. / min with a nitrogen gas flow of 200 ml / min using a thermal analyzer Thermoplus EVOII and a differential type differential thermobalance TG-DTA (manufactured by Rigaku Corporation). After holding at 450 ° C. for 30 minutes, the residue weight is obtained, and the thermal decomposition residue rate can be calculated from the following formula. Pyrolysis residue rate (%) = (residue weight / weight before TG measurement) × 100
[0018] Thermally decomposable monomers include, for example, hydroxy methacrylate monomers. Generally, it is considered desirable for a monofunctional monomer not to have a polar group in order to exhibit thermal decomposition properties. However, as a result of extensive research conducted by the present inventors, it has been discovered that, among methacrylic acid hydroxy monomers, 2-hydroxyethyl methacrylate exhibits thermal decomposition properties superior to those of various other monofunctional monomers, despite having a polar group. The content of the thermally decomposable monomer is preferably 20% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, based on the total amount of the modeling liquid. When the content of the thermally decomposable monomer is 20% by mass or less, the strength and thermal decomposability of the obtained green body can be compatible.
[0019] -Monomers with alicyclic structures in the side chains- Since the strength of the green body is insufficient when made of only 2-hydroxyethyl methacrylate, it is preferable to further add a monofunctional monomer having an alicyclic structure in the side chain to the molding liquid to increase the strength of the green body. Examples of monomers having an alicyclic structure in the side chain include isobornyl (meth)acrylate, (meth)acryloylmorpholine, 4-t-butylcyclohexyl (meth)acrylate, and 3,3,5-trimethylcyclohexyl (meth)acrylate. These may be used alone or in combination of two or more. Among these, (meth)acryloylmorpholine is particularly preferred from the viewpoint of the strength of the green body. The content of the monomer having an alicyclic structure in the side chain is preferably 50% by mass or more, and more preferably 60% by mass or less, based on the total amount of the modeling liquid. When the content of the monomer having an alicyclic structure in the side chain is 50% by mass or more, the strength of the green body can be improved.
[0020] The content of the monofunctional monomer is preferably 70% by mass or less, and more preferably 80% by mass or more, based on the total amount of the modeling liquid. When the content of the monofunctional monomer is 70% by mass or more, the strength and thermal decomposition property of the obtained green body can be compatible.
[0021] <Polyfunctional Monomer> Examples of the polyfunctional monomer include difunctional diacrylates and trifunctional triacrylates, etc. Among these, difunctional diacrylates are preferred because they have a low thickening effect and good ejection properties from an inkjet head. The polyfunctional monomer is not particularly limited and can be appropriately selected depending on the purpose. For example, triethylene glycol diacrylate, tetraethylene glycol diacrylate, pentaerythritol triacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, dipropylene glycol diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polytetramethylene glycol diacrylate, polytetramethylene glycol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, 3-methyl-2-propanediol di ... -methyl-1,5 pentanediol diacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, trimethylolpropane ethoxy triacrylate, glycerol propoxy triacrylate, pentaerythritol tetraacrylate, pentaerythritol alkoxy tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hexaacrylate, and the like. The content of the polyfunctional monomer is preferably 10% by mass or more and 30% by mass or less, and more preferably 10% by mass or more and 20% by mass or less, based on the total amount of the modeling liquid. When the content of the polyfunctional monomer is 10% by mass or more and 30% by mass or less, the strength of the green body can be improved. When the content of the polyfunctional monomer is less than 10% by mass, the effect of crosslinking is small and the strength of the green body may be insufficient, and when it exceeds 30% by mass, the toughness decreases and sufficient strength of the green body may not be obtained.
[0022] The mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is from 65 / 35 to 95 / 5, and preferably from 80 / 20 to 90 / 10. When the mass ratio (A / B) is 65 / 35 to 95 / 5, a green body having excellent strength and thermal decomposition property can be obtained.
[0023] <Thermal polymerization initiator> The modeling liquid of the present invention may contain a thermal polymerization initiator. A thermal polymerization initiator is a compound that generates radicals when heated. By using the polymerization initiator, it is possible to harden the modeling liquid while suppressing oxidation of the metal. As the thermal polymerization initiator, an azo polymerization initiator is preferable because it does not oxidize the metal powder. Examples of the azo polymerization initiator include 2,2'-azoisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)ethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[2-(hydroxymethyl)propionitri], and the like. 1, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobisisobutyric acid dimethyl, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, etc. These may be used alone or in combination of two or more. Among these, 2,2'-azoisobutyronitrile is preferred from the viewpoint of compatibility between the stability over time of the modeling liquid and the reaction temperature. The content of the thermal polymerization initiator is preferably 0.01 parts by mass or more and 5 parts by mass or less, and more preferably 0.1 parts by mass or more and 1 part by mass or less, per 100 parts by mass of reactive monomer (thermally decomposable monomer, monomer having an alicyclic structure, polyfunctional monomer).
[0024] <Other ingredients> The other components are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other components include surfactants, drying inhibitors, viscosity adjusters, penetrating agents, antifoaming agents, pH adjusters, preservatives, antifungal agents, colorants, preservatives, and stabilizers.
[0025] The surfactant is preferably added for the purpose of adjusting the surface tension of the modeling liquid. Examples of the surfactant include anionic surfactants, nonionic surfactants, amphoteric surfactants, acetylene glycol surfactants, fluorine-based surfactants, and silicone-based surfactants.
[0026] It is preferable that the molding liquid of the present invention does not substantially contain water. This allows the powder base material to be applied even if it is a highly active metal, in other words, a water-inhibiting material (e.g., aluminum, titanium, etc.). Note that "substantially does not contain water" means that the water content is preferably 1.0 mass% or less, more preferably 0.1 mass% or less, and even more preferably 0.01 mass% or less, based on the total amount of the molding liquid. It is particularly preferable that the water content in the molding liquid is below the detection limit when a method known and common technical knowledge is used.
[0027] It is preferable that the molding liquid of the present invention does not substantially contain solids such as particles. This stabilizes the discharge from the molding liquid application means such as an inkjet head, and the strength of the cured product formed by applying the molding liquid to the powder layer is sufficiently obtained, and the dimensional accuracy is improved. Note that, "substantially not containing solids" means that the solid content is preferably 1.0 mass% or less, more preferably 0.1 mass% or less, and even more preferably 0.01 mass% or less, based on the total amount of the molding liquid. In addition, it is particularly preferable that the solid content in the molding liquid is below the detection limit when a method known and common technical knowledge is used.
[0028] -How to prepare modeling liquid- The method for preparing the modeling liquid is not particularly limited and can be appropriately selected depending on the purpose. For example, a method in which a thermally decomposable monomer, a polyfunctional monomer, a monomer having an alicyclic structure in a side chain, and a thermal polymerization initiator are added, and further other components as necessary, are mixed and stirred, etc. can be mentioned.
[0029] -Physical properties of modeling liquid- The viscosity of the modeling liquid is preferably 3 mPa·s or more and 20 mPa·s or less, and more preferably 5 mPa·s or more and 10 mPa·s or less, at 25° C. If the viscosity is 3 mPa·s or more or 20 mPa·s or less, the ejection of the modeling liquid from the inkjet nozzle is stabilized, and the strength of the cured product formed by applying the modeling liquid to the powder is sufficient, and the dimensional accuracy is good. The viscosity can be measured, for example, in accordance with JIS K7117.
[0030] The static surface tension of the modeling liquid is preferably 40 N / m or less, more preferably 10 N / m or more and 30 N / m or less, at 25° C. When the static surface tension is 40 N / m or less, ejection from the inkjet nozzle is stabilized, and the strength of the cured product formed by applying the modeling liquid to the powder layer is sufficient, and the dimensional accuracy is good. The static surface tension can be measured, for example, by using DY-300 manufactured by Kyowa Interface Science Co., Ltd.
[0031] (3D modeling kit) The kit for three-dimensional modeling of the present invention contains a powder and a modeling liquid, and further contains other components as necessary.
[0032] <Modeling liquid> As the molding liquid, the molding liquid of the present invention containing a monofunctional monomer and a polyfunctional monomer is used.
[0033] <Powder> As the powder, at least one of a powder of a substrate alone and a powder of a substrate surface coated with an organic material can be used.
[0034] -Base material- The substrate is not particularly limited as long as it has a powder or particle form and can be appropriately selected depending on the purpose. Examples of the material include metals, ceramics, carbon, polymers, wood, biocompatible materials, sand, magnetic materials, etc. These may be used alone or in combination of two or more. Among these, metals and ceramics that can be finally sintered (processed) are preferred from the viewpoint of obtaining a three-dimensional object with extremely high strength.
[0035] The metal is not particularly limited as long as it contains a metal as a material, and examples thereof include magnesium (Mg), aluminum (Al), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), lead (Pd), silver (Ag), indium (In), tin (Sn), tantalum (Ta), tungsten (W), neodymium (Nd), and alloys thereof. These may be used alone or in combination of two or more. Among these, (Fe), copper (Cu), silver (Ag), titanium (Ti), aluminum (Al), and alloys thereof are preferred, and aluminum alloys are more preferred.
[0036] Examples of aluminum alloys include AlSi 10 Mg, AlSi 12 , AlSi7Mg 0.6 , AlSi3Mg, AlSi9Cu3, Scalmalloy, ADC12, etc.
[0037] Examples of ceramics include oxides, carbides, nitrides, and hydroxides. Examples of the oxide include metal oxides, etc. Examples of the metal oxide include silica (SiO2), alumina (Al2O3), zirconia (ZrO2), titania (TiO2), etc.
[0038] The substrate may be a commercially available product, such as pure Al (A1070-30BB, manufactured by Toyo Aluminum Co., Ltd.), pure Ti (Osaka Titanium Technologies Co., Ltd.), SUS316L (PSS316L, manufactured by Sanyo Special Steel Co., Ltd.), AlSI10Mg (Si10MgBB, manufactured by Toyo Aluminum Co., Ltd.), SiO2 (Excelica SE-15K, manufactured by Tokuyama Corporation), AlO2 (Taimei Chemical Industry Co., Ltd., product name: Taimicron TM-5D), ZrO2 (TOSOH Corporation, product name: TZ-B53), etc. The substrate may be subjected to a known surface treatment (surface modification treatment) for the purpose of improving adhesion to organic materials and improving coating properties.
[0039] The volume average particle size of the base material is not particularly limited and can be appropriately selected depending on the purpose, but is preferably, for example, from 2 μm to 100 μm, and more preferably from 8 μm to 50 μm. When the volume average particle diameter of the base material is 2 μm or more, the effect of aggregation is prevented from increasing, the base material is easily coated with an organic material, and a decrease in yield, a decrease in the manufacturing efficiency of the molded object, and a decrease in the handleability and ease of handling of the base material can be prevented. In addition, when the volume average particle diameter is 100 μm or less, a decrease in contact points between particles and an increase in voids can be prevented, and a decrease in the strength of the three-dimensional molded object and its sintered product can be prevented. The particle size distribution of the base material is not particularly limited and can be appropriately selected depending on the purpose, but a sharper particle size distribution is preferable. The volume average particle size and particle size distribution of the base material can be measured using a known particle size measuring device, for example, a particle size distribution measuring device Microtrac MT3000II series (manufactured by Microtrac Bell Co., Ltd.).
[0040] The substrate can be manufactured by a conventionally known method. Examples of methods for manufacturing a powder or particulate substrate include a pulverization method in which a solid is compressed, impacted, or rubbed to be finely divided, an atomization method in which a molten metal is sprayed to obtain a quenched powder, a precipitation method in which a component dissolved in a liquid is precipitated, and a gas-phase reaction method in which a component is vaporized and crystallized. The manufacturing method of the substrate is not limited, but a more preferred method is, for example, atomization, which can obtain a spherical shape and has little variation in particle size. Examples of atomization methods include water atomization, gas atomization, centrifugal atomization, and plasma atomization, and any of them can be suitably used.
[0041] -Organic materials- In the powder having a base material surface coated with an organic material, a resin is preferably used as the organic material. The resin is not limited to the resin that coats the substrate, but also includes the resin that coated the substrate and is dissolved in the modeling liquid. "Coated" refers to a state in which at least a part of the substrate surface is covered with the coating resin, and is not limited to a state in which the entire substrate surface is covered with the resin. "Dissolved in the modeling liquid" refers to, for example, when 1 g of the coating resin material is mixed with 100 g of modeling liquid at 30°C and stirred, 90% or more by mass of the resin is dissolved.
[0042] It is preferable that the resin has low reactivity with highly active metals (highly active metals) that can be used as the substrate. In particular, it is more preferable that the resin is soluble in an organic solvent that has low solubility in water. This allows the resin to be applied even if the substrate is a highly active metal, in other words, a water-inhibiting material (e.g., aluminum, titanium, etc.).
[0043] The resin may have a reactive functional group that reacts with the modeling liquid to form a crosslinked structure. Examples of the reactive functional group include an acrylic group and a vinyl group. Among these, an acrylic group, which has a fast reaction rate, is preferred.
[0044] In order to prevent the resin from remaining in the molded object during the degreasing or sintering process, which would inhibit sintering, it is preferable that 95% by mass or more of the resin be thermally decomposed when heated alone at 450°C.
[0045] The resin is preferably a resin having a hydroxyl group, and examples thereof include polyvinyl acetal (glass transition temperature: 107°C), polyvinyl butyral (glass transition temperature: 67°C), polyacrylic polyol (glass transition temperature: 80°C), polyester polyol (glass transition temperature: 133°C), polybutadiene polyol (glass transition temperature: -17°C), ethyl cellulose (glass transition temperature: 145°C), and nitrocellulose (glass transition temperature: 50°C). Other examples include partially saponified vinyl acetate copolymers (vinyl chloride-vinyl acetate, ethylene-vinyl acetate, etc.), polyether polyols, and phenol-based polyols. These may be used alone or in combination of two or more. Among these, polyacrylic polyols are preferred.
[0046] It is preferable that the resin has many hydroxyl groups within the molecule, not at the molecular terminals, and has a weight average molecular weight and a hydroxyl value of at least a certain level. The weight average molecular weight is preferably 100,000 or less, and more preferably from 2,000 to 100,000. The resin preferably has a weight average molecular weight of 100,000 or less and is a solid at room temperature. The hydroxyl value is more preferably 10 mgKOH / g or more in terms of adhesion to the substrate.
[0047] The resin may be a commercially available product. Examples of the commercially available product include polyacrylic polyol (ACRYDIC WFU-580 manufactured by DIC Corporation), polyester polyol (POLYLITE OD-X-668 manufactured by DIC Corporation, ADEKA NEW ACE YG-108 manufactured by ADEKA Corporation), polybutadiene polyol (GQ-1000 manufactured by Nippon Soda Co., Ltd.), polyvinyl butyral (MOBITAL B20H manufactured by Kuraray Co., Ltd.), polyvinyl acetal (S-LEC BM-2, KS-1 manufactured by Sekisui Chemical Co., Ltd.), ethyl cellulose (ETHOCEL manufactured by Nisshin Seiki Co., Ltd.), and polyacrylic (ORIKOX KC-3000 manufactured by Kyoeisha Chemical Co., Ltd.).
[0048] The average thickness of the resin coating the substrate is preferably 5 nm to 1,000 nm, more preferably 5 nm to 500 nm, even more preferably 50 nm to 300 nm, and particularly preferably 100 nm to 200 nm. When the average thickness is 5 nm or more, the strength of the molded object is improved. Also, when the average thickness is 1,000 nm or less, the dimensional accuracy of the molded object is improved. The average thickness can be obtained, for example, by embedding particles in acrylic resin or the like, exposing the surface of the substrate by etching or the like, and then measuring the thickness at any ten points using a scanning tunneling microscope (STM), an atomic force microscope (AFM), a scanning electron microscope (SEM), or the like, and calculating the average value.
[0049] The ratio of the surface area of the resin to the surface area of the particles (surface coverage) is preferably 15% or more, more preferably 50% or more, and even more preferably 80% or more. When the surface coverage is 15% or more, the strength and dimensional accuracy of the molded object are improved. The surface coverage is measured, for example, by taking a photograph of the powder and measuring any 10 particles that appear in the two-dimensional photograph. Specifically, the ratio (%) of the area of the part covered with resin to the total area of the particle surface is measured, and the average value is calculated and used as the surface coverage. In addition, in determining the part covered with resin, for example, an element mapping method using energy dispersive X-ray spectroscopy such as SEM-EDS can be used.
[0050] The method for producing the powder in which the surface of a substrate is coated with an organic material is not particularly limited and can be appropriately selected depending on the purpose. For example, a method in which an organic material is coated on a substrate according to a known coating method can be preferably used. The method for coating the surface of the substrate with an organic material is not particularly limited and can be appropriately selected from known coating methods, and suitable examples of such coating methods include a rolling fluidized coating method, a spray-drying method, a stirring and mixing addition method, a dipping method, a kneader coating method, etc. In addition, these coating methods can be carried out using various known commercially available coating devices, granulating devices, etc.
[0051] -Powder properties, etc.- The volume average particle size of the powder is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 3 μm or more and 250 μm or less, more preferably 3 μm or more and 200 μm or less, even more preferably 5 μm or more and 150 μm or less, and particularly preferably 10 μm or more and 85 μm or less. When the volume average particle diameter is 3 μm or more, the powder fluidity is improved, the powder (layer) is easily formed, and the smoothness of the laminated layer surface is improved, so that the production efficiency of the three-dimensional object is improved, the handling and handling properties are improved, and the dimensional accuracy tends to be improved. Also, when the volume average particle diameter is 250 μm or less, the size of the space between the powder particles is small, so the porosity of the three-dimensional object is small, which contributes to improving the strength. Therefore, it is preferable for the volume average particle diameter to be 3 μm or more and 250 μm or less in order to achieve both dimensional accuracy and strength. The particle size distribution of the powder is not particularly limited and can be appropriately selected depending on the purpose.
[0052] As a property of the powder, the angle of repose is preferably 60° or less, more preferably 50° or less, and even more preferably 40° or less, when measured. When the angle of repose is 60° or less, the powder can be efficiently and stably arranged at a desired location on the support. The angle of repose can be measured, for example, by using a powder property measuring device (Powder Tester PT-N type, manufactured by Hosokawa Micron Corporation).
[0053] -Other ingredients- Other components in the 3D modeling kit are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other components include a fluidizing agent, a filler, a leveling agent, a sintering aid, and polymeric resin particles.
[0054] A fluidizing agent is preferred because it allows the formation of a powder layer and the like easily and efficiently. Fillers are effective materials for adhering to the surface of powder particles and for filling gaps between powder particles, and have the effect of improving the flowability of powder particles, increasing the number of contact points between powder particles, and reducing the number of gaps, thereby improving the strength and dimensional accuracy of the three-dimensional object. The leveling agent is a material that is effective mainly for controlling the wettability of the powder surface, and has the effect of, for example, increasing the permeability of the modeling liquid into the powder, increasing the strength and speed of the three-dimensional object, and maintaining the shape stably. The sintering aid is an effective material for increasing the sintering efficiency when sintering the obtained cured product (sintering precursor). The effects include, for example, improving the strength of the cured product (sintering precursor), lowering the sintering temperature, and shortening the sintering time.
[0055] The powder can be suitably used for the simple and efficient production of various three-dimensional objects and structures, and can be particularly suitably used in the three-dimensional object production kit of the present invention and the method for producing a three-dimensional object of the present invention. By simply applying the molding liquid of the present invention to powder, a cured product having a complex three-dimensional shape can be produced simply, efficiently, and with good dimensional accuracy. The cured product thus obtained is a green body (sintered precursor) with sufficient hardness, and even if it is held by hand, put in and taken out of a mold, or subjected to an air blowing process to remove excess powder, it does not lose its shape and has excellent handling and handling properties. The cured product may be used as it is, or may be further sintered as a sintered precursor to form a molded product (sintered body of a three-dimensional object).
[0056] (Method of manufacturing three-dimensional objects) The method for producing a three-dimensional object of the present invention includes a modeling liquid application step and a cured product formation step, and preferably includes a degreasing step and a sintering step, and further includes other steps as necessary.
[0057] <Modeling liquid application process> The modeling liquid application step is a step of applying the modeling liquid of the present invention to the powder, and is carried out by a modeling liquid application means. The "modeling liquid" is a liquid composition that has the property of being cured by heat or electron beams, and hardens on the particle surfaces to bond the particles together. Before applying the modeling liquid to the powder, the powder is placed on a support (on a modeling stage) to form a powder layer.
[0058] - Formation of powder layer - There are no particular limitations on the method for disposing powder on a support (on a modeling stage) to form a powder layer, and the method can be appropriately selected depending on the purpose. For example, suitable methods for disposing the powder in a thin layer include a method using a known counter rotation mechanism (flattening roller) used in the selective laser sintering method described in Japanese Patent No. 3607300, a method of spreading the powder into a thin layer using a member such as a brush, roller, or blade, a method of pressing the surface of the powder using a pressing member to spread it into a thin layer, and a method using a known powder additive manufacturing device.
[0059] In order to deposit a thin layer of powder on a support using a counter rotating mechanism, a brush or a blade, a pressing member or the like as a powder layer forming means, the following procedure can be used, for example. That is, the powder is placed on a support arranged within an outer frame (sometimes called a "modeling tank," "mold," "hollow cylinder," "cylindrical structure," etc.) that can be raised and lowered while sliding against the inner wall of the outer frame, using a counter-rotating mechanism or the like. At this time, when a support that can be raised and lowered within the outer frame is used, the support is positioned slightly below the upper opening of the outer frame, that is, positioned below by the thickness of the powder layer, and the powder is placed on the support. In this manner, the powder can be placed in a thin layer on the support.
[0060] In addition, the powder can be placed in a thin layer on the support by using a known three-dimensional object manufacturing device, which can be performed automatically and simply. The three-dimensional object manufacturing device generally includes a recoater (flattening roller) for stacking the powder, a movable supply tank for supplying the powder onto the support, and a movable modeling tank for placing and stacking the powder in a thin layer. In the powder layer modeling device, the surface of the supply tank can always be slightly higher than the surface of the modeling tank by raising the supply tank, lowering the modeling tank, or both, and the powder can be arranged in a thin layer using the recoater from the supply tank side, and the powder can be stacked in a thin layer by repeatedly moving the recoater.
[0061] The thickness of the powder layer is not particularly limited and can be appropriately selected depending on the purpose, but for example, the average thickness per layer is preferably 30 μm or more and 500 μm or less, and more preferably 60 μm or more and 300 μm or less. If the average thickness is 30 μm or more, the strength of the hardened material (sintered precursor) made from the powder (layer) formed by applying the molding liquid to the powder will be sufficient, and problems such as deformation will not occur during subsequent processing such as sintering or handling.If the average thickness is 500 μm or less, the dimensional accuracy of the hardened material made from the powder (layer) formed by applying the molding liquid to the powder will be improved. The average thickness is not particularly limited and can be measured according to a known method.
[0062] The method for applying the modeling liquid to the powder (layer) is not particularly limited and can be appropriately selected depending on the purpose. For example, a dispenser method, a spray method, an inkjet method, etc. can be mentioned. Among these, the dispenser method is excellent in the quantity of droplets, but the coating area is narrow, while the spray method can easily form fine discharged material, has a wide coating area, and is excellent in coating ability, but the quantity of droplets is poor and powder scattering occurs due to the spray flow. For this reason, the inkjet method is particularly preferred in the present invention. The inkjet method has the advantages of being better in the quantity of droplets than the spray method, being able to coat a wider area than the dispenser method, and being preferred in that it can form complex three-dimensional shapes with high precision and efficiency.
[0063] In the case of the inkjet method, the modeling liquid applying means has a nozzle capable of applying the modeling liquid to the powder layer by the inkjet method. As the nozzle, a nozzle (ejection head) in a known inkjet printer can be suitably used, and an inkjet printer can be suitably used as the modeling liquid applying means. As an inkjet printer, for example, SG7100 manufactured by Ricoh Co., Ltd. can be suitably mentioned. An inkjet printer is preferable in that a large amount of modeling liquid can be dropped from the head part at one time and the application area is wide, so that the application can be speeded up. In the present invention, even when an inkjet printer capable of applying the modeling liquid with high precision and efficiency is used, the modeling liquid does not contain solid matter such as particles or highly viscous polymeric materials such as resin, so clogging does not occur in the nozzle or its head, and no corrosion or other problems occur. Furthermore, when the modeling liquid is applied (discharged) to the powder layer, it can efficiently penetrate the organic material in the powder, resulting in excellent efficiency in the production of three-dimensional objects. Moreover, since no polymeric components such as resin are applied, there is no unexpected increase in volume, and it is advantageous in that a cured product with good dimensional precision can be obtained easily and efficiently in a short period of time.
[0064] <Cured product formation process> The hardened product forming step is a step of forming a hardened product by hardening the powder to which the modeling liquid has been applied, and is carried out by a hardened product forming means. "Cured product" refers to a structure in which reactive monomers (thermally decomposable monomers, monomers having an alicyclic structure, and polyfunctional monomers) in the modeling liquid react and become non-fluid, thereby maintaining a certain three-dimensional shape.
[0065] Examples of methods for curing the powder to which the modeling liquid has been applied to form a cured product include heat, electromagnetic waves, electron beams, neutron beams, and a method of mixing two or more materials. Among these, the method of curing with heat is preferred because it is the cheapest and most convenient. In addition, the method of curing with electron beams is preferred because the curing speed of the reactive monomer is fast and the high permeability into the powder allows the formation of a green body with a large thickness.
[0066] The heating temperature in the thermal curing is preferably 100° C. or less. Heating may be performed for each layer, or the cured product forming step of applying the modeling liquid, the cured product forming step of curing by heating, and the lamination step may be repeated. In order to prevent deactivation of radicals generated from the polymerization initiator by heating, the heat curing is preferably carried out in an atmosphere with an oxygen concentration of 5% by volume or less or in an inert atmosphere, such as nitrogen or argon. The pressure of the atmosphere having an oxygen concentration of 5% by volume or less or the inert atmosphere is preferably 0.05 MPa or more and 1.0 MPa or less in order to suppress evaporation of the reactive monomer. The heating method is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a method of putting powder with a modeling liquid into a container set to a certain temperature such as an oven, a method of heating the outer wall of the modeling layer, a method of directly heating the powder or modeling liquid by irradiating with microwaves or infrared rays, or a combination of two or more of these methods. Heating may be performed during modeling.
[0067] The electron beam irradiation is preferably performed using an electron beam irradiation device with an acceleration voltage of 200 kV to 500 kV and a dose of 10 kGy to 500 kGy. Since the electron beam is attenuated by shielding with metal powder, it is preferable to perform the irradiation with an acceleration voltage of 200 kV or more. If the acceleration voltage exceeds 500 kV, the radiation source and the shielding plate become large, and the irradiation device and the modeling device become large. Since the depth that the electron beam reaches is affected by shielding by metal powder, it is preferable to harden each layer at a time. Specifically, a hardened product forming step of applying a modeling liquid, a hardened product forming step of irradiating an electron beam, and a stacking step are repeated to obtain a stacked hardened product. The electron beam irradiation is preferably carried out in air or in an inert atmosphere. The reaction of the reactive monomer proceeds even in air, but when the electron beam is irradiated in air, harmful substances such as ozone are generated, so that it is necessary to purge with an inert gas or to perform sufficient ventilation.
[0068] In the method for producing a three-dimensional object of the present invention, a laminate is formed by sequentially repeating the above-mentioned modeling liquid application step and hardened product formation step (hereinafter referred to as the "lamination step"). The "laminate" is a structure in which multiple powder layers, each having an area to which the modeling liquid has been applied, are laminated.
[0069] The lamination process includes a modeling liquid application process and a hardened material formation process, which are similar to those described above, on a thin layer, which is a layer of powder having an area to which the modeling liquid has been applied, thereby forming an area to which the modeling liquid has been applied in the newly laminated layer of powder. Note that at this time, the area to which the modeling liquid has been applied that is generated in the topmost laminated thin layer of powder is continuous with the area to which the modeling liquid has been applied in the thin layer of powder present below. As a result, an area to which the modeling liquid has been applied that is twice as thick as the powder layer is obtained. When stacking the next powder layer on top of the previous powder layer, the stacking pitch is preferably 50 μm or more and 150 μm or less.
[0070] <Degreasing process> The method for producing a three-dimensional object of the present invention preferably includes a degreasing step in which the green body is heated to remove organic components to obtain a degreased body. The "degreased body" is a three-dimensional object obtained by degreasing organic components such as crosslinked resin from the green body. The cured product, which is the object before the sintering step described below, the green body, and the degreased body are collectively referred to as the "sintering precursor." In the degreasing step, the organic components are decomposed and removed by heating the green body at a temperature equal to or higher than the thermal decomposition temperature of the organic components and lower than the melting point or solidus temperature of the material constituting the base material using a degreasing means such as a known sintering furnace or electric furnace.
[0071] <Sintering process> The sintering step is a step of subjecting the hardened material to a sintering treatment, and is carried out by a sintering means. The sintering step is a step of sintering a three-dimensional object (green body) formed by stacking the hardened products formed in the hardened product forming step. By carrying out the sintering step, the green body can be made into a densified and integrated metal or ceramic molded product (sintered three-dimensional object). The sintering means may be, for example, a known sintering furnace, or may be the same means as the above-mentioned degreasing means. The degreasing step and the sintering step may be carried out consecutively.
[0072] <Other processes> The other steps are not particularly limited and can be appropriately selected depending on the purpose. For example, there are a drying step, an excess powder removing step, a post-treatment step, and the like.
[0073] -Drying process- The method for producing a three-dimensional object of the present invention preferably includes a drying step of drying the green body to remove any liquid components remaining in the green body. The drying step may remove not only liquid components such as organic solvents contained in the green body, but also organic substances. As a drying means, for example, a known dryer, a thermo-hygrostat, etc. may be used.
[0074] -Excess powder removal process- The method for producing a three-dimensional object of the present invention preferably includes an excess powder removing step of removing excess powder adhering to the cured product to obtain a green body. The term "green body" refers to a three-dimensional object that maintains a certain three-dimensional shape by reacting reactive monomers to make the object non-fluid, and that has been subjected to an excess powder removing step of removing excess powder that is not a part of the cured product, and preferably refers to a three-dimensional object to which excess powder does not substantially adhere. Methods for removing excess powder include a method of removing excess powder from a cured product by air blowing, and a method of removing excess powder from a cured product by immersing the product in a removing liquid.
[0075] -Post-processing- The method for producing a three-dimensional object of the present invention preferably includes a post-treatment step for performing post-treatment on the sintered body. The post-treatment step is not particularly limited and can be appropriately selected depending on the purpose. Examples of the post-treatment step include a surface protection treatment step and a painting step.
[0076] The surface protection treatment step is a step of forming a protective layer on a three-dimensional object (green body) in which the cured products formed in the cured product formation step are laminated. By carrying out this surface protection treatment step, the surface of the cured product can be given durability that allows the cured product to be used as is. Specific examples of the protective layer include a water-resistant layer, a weather-resistant layer, a light-resistant layer, a heat-insulating layer, and a glossy layer. Examples of the surface protection treatment means include known surface protection treatment devices, such as a spray device and a coating device.
[0077] The coating process is a process of coating the three-dimensional object (green body) formed by laminating the cured products formed in the cured product forming process. By carrying out the coating process, the green body can be colored in a desired color. Examples of coating means include known coating devices, such as coating devices using a spray, roller, brush, etc.
[0078] Here, a flow of modeling in the manufacturing method of a three-dimensional object of the present invention will be described with reference to Figures 1A to 1E. Figures 1A to 1E are schematic diagrams showing an example of the operation of a manufacturing apparatus for a three-dimensional object used in the manufacturing method of a three-dimensional object of the present invention.
[0079] First, a state in which the first powder layer 30 is formed on the modeling stage of the modeling tank will be described. When forming the next powder layer on the first powder layer 30, as shown in FIG. 1A, the supply stage 23 of the supply tank is raised and the modeling stage 24 of the modeling tank is lowered. At this time, the lowering distance of the modeling stage 24 is set so that the interval (layer pitch) between the upper surface of the powder layer in the modeling tank 22 and the lower part (lower tangent part) of the flattening roller 12 is Δt1. The interval Δt1 is not particularly limited, but is preferably 50 μm or more and 150 μm or less.
[0080] In this embodiment, the flattening roller 12 is disposed so as to create a gap with respect to the upper end surfaces of the supply tank 21 and the modeling tank 22. Therefore, when the powder 20 is transferred and supplied to the modeling tank 22 and flattened, the upper surface of the powder layer is located higher than the upper end surfaces of the supply tank 21 and the modeling tank 22. This reliably prevents the flattening roller 12 from contacting the upper end surfaces of the supply tank 21 and the modeling tank 22, reducing damage to the flattening roller 12. If the surface of the flattening roller 12 is damaged, streaks will occur on the surface of the powder layer 31 (see FIG. 1D) supplied to the modeling tank 22, making it easier for flatness to decrease.
[0081] Next, as shown in FIG. 1B, the powder 20 arranged at a position higher than the upper end surface of the supply tank 21 is moved toward the modeling tank 22 while rotating the flattening roller 12 in the direction of the arrow, thereby transferring and supplying the powder 20 to the modeling tank 22 (powder supply). Furthermore, as shown in FIG. 1C, the flattening roller 12 is moved parallel to the stage surface of the modeling stage 24 of the modeling tank 22, and a layer 31 of powder having a predetermined thickness Δt1 is formed on the modeling tank 22 of the modeling stage 24 (flattening). At this time, the surplus powder 20 not used for forming the powder layer 31 falls into the surplus powder receiving tank 29. After forming the powder layer 31, the flattening roller 12 is moved toward the supply tank 21 and returned (returned) to the initial position (origin position) as shown in FIG. 1D.
[0082] Here, the flattening roller 12 is adapted to be able to move while keeping the distance from the upper end surface of the modeling tank 22 and the supply tank 21 constant. By being able to move while keeping the distance constant, the flattening roller 12 can transport the powder 20 onto the modeling tank 22, while forming a powder layer 31 of uniform thickness h (corresponding to the layer pitch Δt1) on the modeling tank 22 or on the already formed hardened layer 30. In the following, the thickness h of the powder layer 31 and the layer pitch Δt1 may be described without distinction, but unless otherwise specified, they are the same thickness and have the same meaning. The thickness h of the powder layer 31 may also be obtained by actually measuring it, and in this case, it is preferable to use the average value of a plurality of points.
[0083] 1E, droplets 10 of the modeling liquid are discharged from the head 52 of the liquid discharge unit to form a layer 30 to which the modeling liquid is applied having a desired shape on the next powder layer 31 (modeling). Next, the above-mentioned powder layer forming process and modeling liquid applying process are repeated to form and stack a new layer 30 to which the modeling liquid is applied. At this time, the new layer 30 to which the modeling liquid is applied and the layer 30 to which the modeling liquid is applied underneath it are integrated. Thereafter, the powder layer forming process and modeling liquid applying process are further repeated to complete the stacked product. EXAMPLES
[0084] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0085] (Monomer Liquid Preparation Examples 1 to 6) The monofunctional monomers shown in Table 1 were mixed with a magnetic stirrer for 5 minutes, and then the thermal polymerization initiators shown in Table 1 were added and further mixed with a magnetic stirrer for 120 minutes to be fully dissolved. The resulting monomer liquid was filtered through a disposable membrane filter (28CP020AS, manufactured by Advantec Co., Ltd.) to prepare monomer liquids No. 1 to 6. The blending amount of each component in Table 1 is in parts by mass.
[0086] <Measurement of pyrolysis residue rate of monomer liquid> 2 g of the resulting monomer solutions No. 1 to 6 were placed in a Teflon (registered trademark) petri dish with a diameter of 5 cm and treated for 6 hours in a constant temperature bath at 80°C filled with nitrogen gas and adjusted to an oxygen concentration of 5 volume% or less to obtain a resin film. 8 mg of the obtained resin film was weighed out and heated from 50°C to 450°C at a rate of 20°C / min with a nitrogen gas flow of 200 ml / min using a thermal analyzer, Thermoplus EVOII differential thermobalance TG-DTA (manufactured by Rigaku Corporation). After holding at 450°C for 30 minutes, the weight of the residue was determined and the thermal decomposition residue rate was calculated using the following formula. The results are shown in Table 1. Pyrolysis residue rate (%) = (residue weight / weight before TG measurement) × 100
[0087] [Table 1]
[0088] Details of each component in Table 1 are as follows. *HEMA: 2-hydroxyethyl methacrylate (Kyoeisha Chemical Co., Ltd.) *LA: Lauryl acrylate (Kyoeisha Chemical Co., Ltd.) *ACMO: Acryloylmorpholine (KJ Chemicals Co., Ltd.) *IBXA: Isobornyl acrylate (Osaka Organic Chemical Co., Ltd.) *TBCHA: 4-t-butylcyclohexyl acrylate (manufactured by Sartomer) *TMCHA: 3,3,5-trimethylcyclohexyl acrylate (manufactured by Sartomer) *AIBN: 2,2'-azobis(isobutyronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0089] The results in Table 1 show that 2-hydroxyethyl methacrylate (HEMA) exhibits thermal decomposition properties superior to those of various other monofunctional monomers.
[0090] (Examples 1 to 14 and Comparative Examples 1 to 5) <Preparation of modeling liquid> The thermally decomposable monomers and monomers having an alicyclic structure in the side chain shown in Tables 2 to 5 were mixed with a magnetic stirrer for 5 minutes, and then the polyfunctional monomers shown in Tables 2 to 5 were mixed with a magnetic stirrer for 30 minutes to be fully dissolved. Thereafter, a thermal polymerization initiator was added, and the mixture was further mixed with a magnetic stirrer for 120 minutes to be fully dissolved. The obtained solution was filtered through a disposable membrane filter (28CP020AS, manufactured by Advantec Co., Ltd.) to prepare the molding solutions of Examples 1 to 14 and Comparative Examples 1 to 5. The blending amounts of each component in Tables 2 to 5 are in parts by mass.
[0091] <Measurement of pyrolysis residue rate of modeling liquid> 2 g of each of the molding liquids shown in Tables 2 to 5 was placed in a Teflon (registered trademark) petri dish with a diameter of 5 cm, and treated for 6 hours in a constant temperature bath at 80°C filled with nitrogen gas to adjust the oxygen concentration to 5% by volume or less, to obtain a resin film. 8 mg of the obtained resin film was weighed out, and the temperature was raised from 50°C to 450°C at a rate of 20°C / min with a nitrogen gas flow of 200 ml / min using a thermal analyzer Thermoplus EVOII differential thermobalance TG-DTA (manufactured by Rigaku Corporation). After holding at 450°C for 30 minutes, the weight of the residue was determined, and the thermal decomposition residue rate was calculated using the following formula. The results are shown in Tables 2 to 4. Pyrolysis residue rate (%) = (residue weight / weight before TG measurement) × 100
[0092] <Creating objects> AlSi as powder10 Using Mg powder (manufactured by Toyo Aluminum KK, Si10Mg-30BB, volume average particle size: 35 μm) and the molding liquids of Examples 1 to 14 and Comparative Examples 1 to 5, green bodies were produced as follows. In Example 12, a resin-coated metal powder prepared as follows was used as the powder, and the modeling liquid of Example 12 was used. -Preparation of coating solution- 6 parts by mass of acrylic polyol resin (TZ#9515, manufactured by Toei Kasei Co., Ltd.) was mixed with 114 parts by mass of acetone, and while heating to 50°C in a water bath, the mixture was stirred for 1 hour using a Three-One Motor (BL600, manufactured by Shinto Scientific Co., Ltd.) to dissolve the acrylic polyol in an organic solvent, and 120 parts by mass of a 5% by mass acrylic polyol solution was prepared. The resulting prepared solution was used as a coating solution. The viscosity of the 5% by mass solution of acrylic polyol at 20°C was measured using a viscometer (Rotational viscometer, DV-E VISCOMETER HADVE115, manufactured by Brookfield) and was 5.0 mPa·s to 6.0 mPa·s. Next, a commercially available coating device (Powrex, MP-01) was used to coat the AlSi 10 The coating liquid was applied to 100 parts by mass of Mg powder (manufactured by Toyo Aluminum K.K., Si10Mg-30BB, volume average particle size: 35 μm) so that the coating resin was 1 part by mass, to prepare a metal powder.
[0093] (1) Using a three-dimensional object manufacturing device such as that shown in Figures 1A to 1E, powder was transferred from the supply-side powder storage tank to the modeling-side powder storage tank, and a thin layer of powder with an average thickness of 84 μm was formed on the support. (2) Next, the modeling liquid was discharged from the nozzle of a known inkjet discharge head onto the surface of the thin layer of powder that had been formed. The discharge area of the modeling liquid was a rectangle of 40 mm x 10 mm, and the amount of modeling liquid per voxel was 36 pL at 300 dpi. (3) Next, the above steps (1) and (2) were repeated until the total average thickness reached the predetermined 3 mm, and thin powder layers were successively laminated to form a laminate, which was then heated at 80°C for 6 hours using a dryer (manufactured by Yamato Scientific Co., Ltd., DP300) to form a hardened product. Thereafter, excess powder was removed to obtain green bodies of Examples 1 to 14 and Comparative Examples 1 to 5.
[0094] <Method of measuring bending strength> The bending strength of each of the obtained green bodies was measured as follows. A universal testing machine (Autograph, Model AG-I, manufactured by Shimadzu Corporation) was used to measure the bending strength of the green bodies, along with a 1 kN load cell and a three-point bending jig. The distance between the supports was set to 24 mm, and the stress when the load point was displaced at a speed of 1 mm / min was plotted against the amount of strain, with the stress at the breaking point being taken as the maximum stress. The green bodies were used for the measurement after removing excess powder with a spatula.
[0095] [Table 2]
[0096] [Table 3]
[0097] [Table 4]
[0098] [Table 5]
[0099] Details of each material of the modeling liquid in Tables 2 to 5 are as follows. -Monofunctional monomers and thermal polymerization initiators- As explained in Table 1.
[0100] -Polyfunctional Monomers *3EGDA: Triethylene glycol diacrylate (Kyoeisha Chemical Co., Ltd.) *4EGDA: Tetraethylene glycol diacrylate (Kyoeisha Chemical Co., Ltd.) *PE3A: Pentaerythritol triacrylate (Kyoeisha Chemical Co., Ltd.)
[0101] The results in Tables 1 to 5 show that Examples 1 to 3 and 7 to 8 have excellent thermal decomposition properties and bending strength in the green body because they contain the appropriate amount of the thermally decomposable monomer 2-hydroxyethyl methacrylate (HEMA) and the polyfunctional monomer. Examples 4 to 6 used monomers having an alicyclic structure in the side chain other than acryloylmorpholine (ACMO) in Example 1, and although the bending strength of the green bodies was slightly inferior to that of Example 1, it was found that the green bodies had sufficient thermal decomposition properties and bending strength. Examples 9 and 10 used a polyfunctional monomer different from the polyfunctional monomer (3EG-DA) of Example 1, and although Example 9 had a slightly decreased bending strength of the green body due to an increase in the number of carbon atoms in the crosslinked portion, it was found to have sufficient bending strength. Also, Example 10 used a trifunctional polyfunctional monomer, which had a large thickening effect, so it was necessary to suppress the content of the polyfunctional monomer, and as a result, the content of acryloylmorpholine (ACMO) increased, so the thermal decomposition property of the green body was slightly decreased, but it was found to have sufficient thermal decomposition property.
[0102] In contrast, in Comparative Example 1, the thermal decomposition property of the green body was poor because the modeling liquid did not contain 2-hydroxyethyl methacrylate (HEMA), which is a thermally decomposable monomer. In Comparative Example 2, the content of the polyfunctional monomer in the modeling liquid was too high, resulting in the green body being brittle and lacking in bending strength. In Comparative Example 3, since the modeling liquid did not contain a polyfunctional monomer, the bending strength of the green body was insufficient. In Comparative Example 4, the content of 2-hydroxyethyl methacrylate (HEMA), which is a thermally decomposable monomer, in the modeling liquid was low, and as a result, the thermal decomposition property of the green body was poor. In Comparative Example 5, the content of the polyfunctional monomer in the modeling liquid was low, and as a result, the bending strength of the green body was insufficient.
[0103] From the above results, it was found that when the thermal decomposition residue rate of the resin film of the modeling liquid is high, the thermal decomposition property of the resin film of the modeling liquid deteriorates, which in turn deteriorates the thermal decomposition property of the green body.
[0104] For example, aspects of the present invention are as follows. <1> A modeling liquid containing a monofunctional monomer and a polyfunctional monomer, The monofunctional monomer includes a thermally decomposable monomer, a mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is 65 / 35 to 95 / 5; The molding liquid is characterized in that the rate of pyrolysis residue in the resin film of the molding liquid is 5.0 mass % or less. <2> The content of the thermally decomposable monomer is 20% by mass or less. <1> 2. The molding liquid according to claim 1 . <3> The thermally decomposable monomer is a hydroxy methacrylate monomer. <1> from <2> 10. The molding liquid according to claim 9, <4> The thermally decomposable monomer is 2-hydroxyethyl methacrylate. <3> 2. The molding liquid according to claim 1 . <5> The polyfunctional monomer is a bifunctional monomer. <1> from <4> 10. The molding liquid according to claim 9, <6> The copolymer further contains 50% by mass or more of a monomer having an alicyclic structure in a side chain. <1> from <5> 10. The molding liquid according to claim 9, <7> The monomer having an alicyclic structure in a side chain is (meth)acryloylmorpholine. <6> 2. The molding liquid according to claim 1 . <8> The above-mentioned contains a thermal polymerization initiator. <1> from <7> 10. The molding liquid according to claim 9, <9> For the powder, <1> from <8> A forming liquid application step of applying the forming liquid according to any one of the above items; a hardened product forming step of hardening the powder to which the modeling liquid has been applied to form a hardened product; The present invention relates to a method for producing a three-dimensional object, comprising the steps of: <10> The powder is at least one of a powder of a substrate alone and a powder of a substrate surface coated with an organic material. <9> 2. A method for producing a three-dimensional object according to claim 1 . <11> The substrate includes at least one of a metal and a ceramic. <10> 2. A method for producing a three-dimensional object according to claim 1 . <12> The method includes a sintering step of subjecting the cured product to a sintering treatment. <9> from <11> 10. A method for producing a three-dimensional object according to claim 9, <13> Powder and The above <1> from <8> and a modeling liquid according to any one of the above items. <14> The powder is at least one of a powder of a substrate alone and a powder of a substrate surface coated with an organic material. <13> The present invention relates to a kit for three-dimensional modeling. <15> The substrate includes at least one of a metal and a ceramic. <14> The present invention relates to a kit for three-dimensional modeling.
[0105] The above <1> from <8> The molding liquid according to any one of <9> from <12> The method for producing a three-dimensional object according to any one of the preceding claims, <13> from <15> According to the kit for three-dimensional modeling described in any one of the above, the conventional problems can be solved and the object of the present invention can be achieved. [Prior art documents] [Patent documents]
[0106] [Patent Document 1] Patent No. 4624626
Claims
1. A modeling liquid containing a monofunctional monomer and a polyfunctional monomer, The monofunctional monomer includes a thermally decomposable monomer, a mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is 65 / 35 to 95 / 5; The content of the thermally decomposable monomer is 5% by mass or more and 20% by mass or less, A molding liquid for forming a green body used in three-dimensional modeling, characterized in that a rate of pyrolysis residue in a resin film of the molding liquid is 5.0 mass % or less.
2. The modeling fluid of claim 1 , wherein the thermally decomposable monomer is a hydroxy methacrylate monomer.
3. The molding liquid according to claim 2, wherein the thermally decomposable monomer is 2-hydroxyethyl methacrylate.
4. The molding liquid according to claim 1 , wherein the polyfunctional monomer is a bifunctional monomer.
5. A modeling liquid containing a monofunctional monomer and a polyfunctional monomer, The monofunctional monomer includes a thermally decomposable monomer, a mass ratio (A / B) of the content A of the monofunctional monomer to the content B of the polyfunctional monomer is 65 / 35 to 95 / 5; The rate of pyrolysis residue in the resin film of the modeling liquid is 5.0 mass% or less, A molding liquid for forming a green body used in three-dimensional modeling, further comprising 50% by mass or more and 75% by mass or less of a monomer having an alicyclic structure in a side chain.
6. The molding liquid according to claim 5 , wherein the monomer having an alicyclic structure in a side chain is (meth)acryloylmorpholine.
7. The molding liquid according to claim 1 , further comprising a thermal polymerization initiator.
8. A modeling liquid application step of applying the modeling liquid according to any one of claims 1 to 7 to a powder; a hardened product forming step of hardening the powder to which the modeling liquid has been applied to form a hardened product; A method for producing a three-dimensional object, comprising:
9. The method for manufacturing a three-dimensional object according to claim 8 , wherein the powder is at least one of a powder of a base material alone and a powder of a base material having a surface coated with an organic material.
10. The method for manufacturing a three-dimensional object according to claim 9 , wherein the base material includes at least one of a metal and a ceramic.
11. The method for producing a three-dimensional object according to claim 8 , further comprising a sintering step of sintering the cured product.
12. Powder and A three-dimensional object forming kit comprising the modeling liquid according to claim 1 .
13. The kit for three-dimensional object formation according to claim 12 , wherein the powder is at least one of a powder of a base material alone and a powder of a base material having a surface coated with an organic material.
14. The kit for three-dimensional object fabrication according to claim 13 , wherein the base material includes at least one of a metal and a ceramic.
Citation Information
Patent Citations
Apparatus and method for manufacturing three-dimensional metallic object
JP2005120475A
Liquid set for three-dimensional molding, manufacturing method of three-dimensional object, manufacturing device of three-dimensional object and hydrogel molding body
JP2017105154A
Curable composition, printed matter, adhesive label, housing container, method and device for forming two-dimensional or three-dimensional image, cured article, structure, and molding processed article
JP2020152800A
Powder material for producing three-dimensional object, kit for producing three-dimensional object, and method and apparatus for producing three-dimensional object
JP2021011107A
Material systems and 3D printing methods
JP4624626B2